(untitled) (Journal of the College of Basic Education, 2023)
The research dealt with the expressive abstract pattern in the works of the artist Balasm Muhammad Jassam and how to employ it in his artistic work, as each artist has his own System that reflects his personality and is unique in him and distinguishes him from others through his artistic production. The experience of the artist Balasm Muhammad is one of the experiences that maneuver in its formal, color and tactile elements a game of contrast and polarity between expression, abstraction, diagnostic, non-diagnostic, rough and soft, which resulted in a stylistic construct that relies on the energy of expression and abstraction in a systemic container. As for the importance of the research, it was to supply the technical library of researchers and scholars in academic and cultural institutions with technical information and to benefit from it from an intellectual and creative point of view. As for the objectives of the research, it is summed up in revealing the abstract expressive pattern in the works of the artist, Balasem Muhammad Jassam. The limits of the research were limited to the period between 2010-2019, by adopting the artist’s artworks with the definition of some terms. The second chapter included three sections about me, the first of which is with the format as a concept and the second topic in It was represented by the stylistic pattern of Abstract Expressionism, and the third topic was the stylistic pattern in the works of the artist Balasm Muhammad. The third chapter represented the procedures followed in the community, the analysis of samples and the adoption of the descriptive analytical method, as well as the analysis system as a tool for research. The fourth chapter included the results, conclusions, some recommendations, suggestions, and a list of sources.